Frontline Leadership in Communicating Organizational Policies and its Mediating Influence on Employee Commitment in Nonprofit Organizations in Monrovia, Liberia - Frank O. Bannor; Derrick O. Deya; Josephine Ganu (Pan-African Journal of Education and Social Sciences)
This study examined the influence of frontline leadership communication on employee commitment within nonprofit organizations in Monrovia, Liberia. Four key questions guided the research: (1) perceptions of leaders’ communication and transparency, (2) commitment levels, (3) the relationship between communication, transparency, and commitment, and (4) the mediating role of transparency. Data from 388 respondents show that employees perceive communication and transparency positively. A strong positive correlation (r=0.891, p < 0.001) was found between these factors and commitment, which predicted 82.5% of the variance. The Sobel test confirms that transparency mediates this relationship (z = 7.403, p < 0.001). This highlights the importance of strategic communication in enhancing employee commitment. Recommendations include broadening the study’s scope to determine if the findings are applicable across various cultural and organizational contexts.